Multiple Authorisation: The Legal Complexity of Desentralisasi in Indonesia and the Potential Contribution of IIAs in Reducing Confusion - Ewing-Chow, Michael; Losari, Junianto James (UI Scholars Hub, 2015)
Decentralisation system in Indonesia was introduced after the fall of the former President Soeharto with the objective of ensuring good governance and equitable development across all regions in the country. Unfortunately, the implementation of desentralisasi has been complicated. Some scholars have suggested that the model was flawed as it did not consider Indonesia’s context of less developed administrative institutions in the regions. Not only did desentralisasi cause headaches for the government, it also created confusion for foreign investors. Consequently, it affects the investment climate in the country and undermines the perception of Indonesia as an attractive place to invest in. In certain cases, desentralisasi has also led to claims by foreign investors for investor-State arbitration under Indonesia’s international investment agreements (IIAs). This paper analyses the problems of desentralisasi in Indonesia, its effects to foreign investors and suggests ways to alleviate the problems by modifying and using Indonesia’s IIAs effectively.